Commons, Veblen and Inequalities: Looking Up or Down? (Global Journal of Human-Social Science, 2021)
The aim of this article is to show that, even if both Commons and Veblen denounce the increase in inequalities, they do not approach the issue from the same angle. Linking together those at the top of the social ladder and the lower classes, Commons is primarily concerned with the latter. A real improvement in their lot requires a correction of the excesses of capitalism. Veblen, on the contrary, focuses on the dominant classes whom he opposes to the "common men". He attacks them by accusing them of being responsible for systemic dysfunctions. However, the waste of resources they cause is not directly associated with the emergence of social misery. In the end, the poor find themselves on the periphery of his model.